Atmospheric and Oceanic Pathways Drive Separate Modes of Southern Hemisphere Climate in Simulations of Spontaneous Dansgaard‐Oeschger‐Type Oscillations - Irene Trombini; Nils Weitzel; Paul J. Valdes; Jean‐Philippe Baudouin; Edward Armstrong; Kira Rehfeld (Geophysical Research Letters)
Abstract Dansgaard‐Oeschger (DO) events are a dominant mode of millennial‐scale climate variability during the last glacial period with most pronounced impacts in the North Atlantic region. In Antarctica, they manifest primarily as a muted and phase‐shifted temperature signal, but recent studies suggest an additional in‐phase component. Here, we analyze the Southern Hemisphere (SH) response to spontaneous DO‐type oscillations in a general circulation model. The dominant Antarctic temperature mode is phase‐shifted compared to Greenland temperature variations and consistent with the oceanic pathway described by the bipolar seesaw model. However, the leading SH atmospheric circulation mode varies synchronously with Greenland temperatures. A westward‐shifted Walker circulation and strengthened Hadley cell during Greenland temperature maxima cause zonally heterogeneous jet stream anomalies differing from the Southern Annular Mode pattern. Comparison of simulated δ18O with speleothems and ice cores indicates a good agreement in the tropics and SH mid‐latitudes but deviations in Antarctica warrant further research.